Performance Analysis of Optical Wireless Channel Based on Beamforming Techniques Using Advanced Modulation Schemes - Lwaa Faisal Abdulameer; Adil Fadhil Mushatet; Tania Tariq Salim (Tikrit Journal of Engineering Sciences)
The need for a very high data rate in the next-generation wireless network is growing, and optical wireless communication has become one of the best options for addressing this important problem. The optical system endures power and bandwidth losses due to channel turbulence, particularly in the extreme channel conditions found in outdoor locations. However, suitable advanced optical modulation schemes categorized according to the appropriateness of power efficiency and suitability of bandwidth-efficient systems are used to ensure transmission reliability. In this study, orthogonal frequency-division multiplexing, generalized frequency-division multiplexing, and L-pulse position modulation are used. Utilizing the cutting-edge GFDM-Beamforming technology for the optical wireless channel was to increase the signal to noise ratio and enhance the bit error rate across the board. Gamma-Gamma distribution has been used to compute the bit error rate and spectral efficiency. An arbitrary number of light-emitting diodes and photo-detectors are used at the sources and detectors. The findings demonstrated that the optical generalized frequency-division multiplexing performs better than other modulation schemes in terms of power and bandwidth requirements, with a high peak-to-average-power-ratio, which is the primary drawback in orthogonal frequency-division multiplexing mitigated by the beamforming function.